Türkiye’de 1919-1927 yılları arasında aile hukuku alanındaki kanunlaştırma çalışmaları - Akdoğan, Abdullah (My University, 1999)
OF THE THESIS Family law was not included in the Mecelle which was compiled as the civil code during the codification efforts which dates back on the Ottoman Reformation, commonly knowm as Tanzimat. In the field of Family Law until Personal Regulations Committee the most important devolopments consisted of the 1298/ 1881 Demografic Files İnstructions and the 1332/ 1917 Family Act. After the family Act a new period has commenced. The Abolition of Monarchy in 1922 and the Lozan Coference reflect the legal approach of the nem Turkish state after the establishment of the Grand National Assembly on April 23, 1920 and the announcement of the 1921 constitution. The minorities insisted on maintaining their legal privilegas arguing that the Ottoman State was based on religious law. Against this, the Ankara Government defended the Mecelle and the Family Act by recognizing them modern laws. Furthermore, the Ankara Government considered the legal privileges given to minorities against its independence. But on the insistence of the Allied Powers, it promised to issuc a modern and secular family law. Yet the Allied Powers did not consider this satisfactory. They presented a declaration to the Turkish representatives titled as The Declaration on the Judicial Powers Concerning Non-Personal Affairs. According the this declaration, the judges to be selected from among the members of the Lahey İnternational Court of Justice were to work in the local courts of İstanbul, İzmir and Bursa (Article,5) as well as in the Supreme Court. They would also be employed in the efforts for legal reforms (Article,7). While negotiations continued in Lozan, the new committees had been established. The work of these committees were slow. These committees were called of after 16 meetings probably because the Lozan Act was signed. We see that after the Lozan Conference the advocates of adopting western lams gained more power. Consequently, first, the establish ment of the Republic was announced, the Khilafah was abolished, religious courts were olased, Integration of Education Act was passed as a law, religious scools, mystical institutions were closed, the Ministry of Foundations and Religious Affairs was closed, and the 1340/ 1924 constitution was issued. Following these devolopments, new committiees were set up adopting a revolutionary approach to the issue. The main purpose was to produce laws that arc in harmony with the understanding of modern state. Secular laws were produced concerning different social, religious, and cultural aspects of life. These historical developments in the legal history of Turkey show that the reformation that had began with Tanzimat during the Ottoman State has been culminated by the Turkish Republic. This process marks the end of the efforts to reform the Islamic law from inside. It also marks the end of the efforts to produce a national law from traditional laws.
Keywords: AİLE HUKUKU